Self-healing epoxy via epoxy–amine chemistry in dual hollow glass bubbles - Zhang, He (2014)
Etched hollow glass bubbles (HGBs) with through-holes at micron level were used as micro-containers for epoxy and amine solution to realize the self-healing functionality in epoxy matrix. The average diameter, the average shell thickness, as well as the cavity inside the shell were investigated. In order to check the mechanical robustness and the rupturability of the HGBs, micro-compression tests of single HGB were conducted to measure their mechanical responses, which reveal the relatively high compressive strength and brittle feature. A new type of self-healing epoxy was developed based on the dual HGB carriers and the self-healing performance was optimized systematically to obtain better healing behavior. It is found the highest healing efficiency of about 62% was achieved at 50 °C for 24 h when 12.5 - 15.0 wt% healing agent carriers was incorporated at the optimized ratio of 4 : 1 for epoxy loaded HGBs (HGB-E) to amine loaded HGBs (HGB-A). It is also found that the healing efficiency increased with increased healing duration at 50 °C. In addition, the fracture toughness is improved and the tensile modulus keeps constant while the tensile strength is deteriorated by the incorporation of the carriers.